2017
DOI: 10.1080/14606925.2017.1352820
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing textile enterprises for a more sustainable society, through design research and website development

Abstract: Handmade textile production in Thailand has qualities that accord with sustainability. It is an intangible cultural heritage and a resourceful element for presenting the national identity of Thailand. However, handmade textile production and experienced weavers have been in severe decline. There is the potential loss of weaving skills and knowledge being transferred to younger generations. Design can help to foster a sustainable future of handmade textile producers. This research focused on design for marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…In this paper, we mapped the field of felting from the material perspective and identified the themes of felt-making. Although previous craft and design studies have tackled similar issues (Nimkulrat, 2012;Tung, 2012), only recently have holistic approaches emerged (Laamanen, 2016;Chudasri & Saksrisathaporn, 2017). From a holistic perspective, our study showed that, for felting, the capacities of the material are almost as important as the maker's conscious decisions and intentions since felt makers make sense of their practice through their material interaction.…”
Section: Understanding the Field Of Felting From The Materials Perspecmentioning
confidence: 61%
“…In this paper, we mapped the field of felting from the material perspective and identified the themes of felt-making. Although previous craft and design studies have tackled similar issues (Nimkulrat, 2012;Tung, 2012), only recently have holistic approaches emerged (Laamanen, 2016;Chudasri & Saksrisathaporn, 2017). From a holistic perspective, our study showed that, for felting, the capacities of the material are almost as important as the maker's conscious decisions and intentions since felt makers make sense of their practice through their material interaction.…”
Section: Understanding the Field Of Felting From The Materials Perspecmentioning
confidence: 61%
“…Twelve types of traditional crafts are set to be examples, and are analyzed with regard to two variables: "the way in which knowledge is transmitted and the degree of experimentation facilitated by the activity". The study concluded that domestication of traditional crafts is one of the approaches suitable for revitalization by amateurs, and has disclosed six domestication strategies that can be arranged into two broad categories: (5) A-Fixed and ( documented or interactive or live.) B-Experimental and ( documented or interactive or live).…”
Section: Introductionmentioning
confidence: 99%